Recommendations of the VAC2VAC workshop on the design of multi-centre validation studies. (March 2018) - Halder, Marlies; Depraetere, Hilde; Delannois, Frédérique; Akkermans, Arnoud; Behr-Gross, Marie-Emmanuelle; Bruysters, Martijn; Dierick, Jean-François; Jungbäck, Carmen; Kross, Imke; Metz, Bernard; Pennings, Jeroen; Rigsby, Peter; et al.
Abstract: Within the Innovative Medicines Initiative 2 (IMI 2) project VAC2VAC (Vaccine batch to vaccine batch comparison by consistency testing), a workshop has been organised to discuss ways of improving the design of multi-centre validation studies and use the data generated for product-specific validation purposes. Moreover, aspects of validation within the consistency approach context were addressed. This report summarises the discussions and outlines the conclusions and recommendations agreed on by the workshop participants. Highlights: In Europe, use of non-animal methods is encouraged and being informed is key. Manufacturers should engage in validation studies at an early stage. Participants in validation studies can use data for product-specific validation. More regulatory guidance on setting specifications and validity criteria needed. Communication of key players crucial for implementation/acceptance of methods.